Faktor Pendukung Keberhasilan Belajar Bahasa Inggris - Diemroh Ihsan (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2005)
This study describes some faktors that make individuals successful in learning English based on research done using questionnaire as the instrument. Ninety three respondents consisting of students, teachers, and lecturers of English, and lecturers of non-English majors who returned the questionnaires were used as the sample. The questionnaires were analyzed using the simplest form of statistical analysis-percentages-with qualitative explanation. The result shows, among others, that (1) 82% of the respondents state that they succeed learning English because they themselves want to learn it as they realize they need it; (2) 63% claim that they learn English successfully through English courses; and (3) the appropriate modes of teaching to enhance student autonomy in learning are group discussion and seminar procedures --51% and 47%, respectively.